1977
DOI: 10.1104/pp.60.4.635
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lanthanum and Ethylenediaminetetraacetate on Leaf Movements of Mimosa

Abstract: Lanthanum and ethylenediaminetetraacetate (EDTA) profoundly affect the rapid leaf movements of Mimosa pudica L. Lanthanum, which mimics calcium but does not penetrate the plasmalemma, inhibits the dosing response but does not affect reopening. A low concentration of EDTA retards the reopening process while a higher EDTA concentration prevents the dosing movement. There is evidence that the EDTA effects result from chelation of calcium ions rather than chelation of other cations. These results are discussed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 14 publications
(21 reference statements)
0
29
0
Order By: Relevance
“…On the basis that motility is inhibited by chelatants (EDTA and EGTA) (4,13,19) and promoted by the ionophore A 23187 (19), it can be supposed that calcium is involved in the regulation of leaf movements induced by variations in light conditions; in fact, fluxes of Ca2+ from the wall to the cellular interior have been reported during seismonastic movements of M. pudica (28). Until now, the mechanism of calcium mediation has not been clearly understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis that motility is inhibited by chelatants (EDTA and EGTA) (4,13,19) and promoted by the ionophore A 23187 (19), it can be supposed that calcium is involved in the regulation of leaf movements induced by variations in light conditions; in fact, fluxes of Ca2+ from the wall to the cellular interior have been reported during seismonastic movements of M. pudica (28). Until now, the mechanism of calcium mediation has not been clearly understood.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, it is suggested that calcium is not mobilized Since Ca2" is necessary to the response (4,19), it is postulated (28) that Ca2+ is taken from internal stores which may be the tannin vacuole and/or the endoplasmic reticulum. This can be achieved through involvement of the phosphatidylinositol pathway as described by Berridge and Irvine (2); this proposal is not unreasonable considering that the major metabolites of the phosphatidylinositol cycle have been separated from extracts of Samanea saman pulvini (14) and, furthermore, a short treatment with white light elicits a rapid change in the cycle components in these motor organs (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9) indicates that the net transport of Ca2+ is small relative to Ca2+/Ca2+ exchange. (3,18) and animals (2). K+ was less effective in replacing surface-bound Ca24, as indicated by the total 'Ca2+ and the difference between water and CaCl2 at 10-min values.…”
mentioning
confidence: 99%
“…11 Calcium is known as one of the ions involves in leaf movements. 12,13 Calcium uptake and transport from root to shoots take place through transpiration stream, 14 and its absorption and transport reported to be by passive diffusion and exchange reactions. 15,16 Sorooshzadeh et al 17 reported displacement of 45 Ca through leaf via mid-rib and secondary veins of soybean.…”
Section: Introductionmentioning
confidence: 99%